Revitalisasi Posyandu dan Menghidupkan Tanaman Obat sebagai Solusi Kesehatan Alternatif Masyarakat Sawangan Elok di Masa Pandemi COVID-19 - Arief, Rachmat; Wahyuni, Endah Sri (PT Hakhara Akademia Indonesia, 2023)
The activity of revitalizing the posyandu and reviving medicinal plants as an alternative health solution for the Sawangan Elok community during the COVID-19 pandemic aims to foster public awareness and sensitivity towards the environmental health of the Sawangan Elok community and provide comfort for people who seek treatment at the Sawangan Elok posyandu. This community service activity in the form of revitalizing the posyandu and reviving medicinal plants as an alternative health solution for the Sawangan Elok community during the COVID-19 pandemic was able to run smoothly with three activities in the form of rearranging the fence, planting family medicinal plants, and repainting the posyandu walls.